2021
DOI: 10.1038/s41598-021-90397-y
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation and pro-inflammatory cytokine profile predict response to checkpoint inhibitor treatment in NSCLC: a prospective study

Abstract: Treatment with single agent immune checkpoint inhibitors (ICIs) has tremendously changed second line therapy in NSCLC. However, there are still no reliable biomarkers predicting response and survival in this group of patients. PD-L1 revealed to be a correlating, but no perfect marker. Therefore, we sought to investigate in this prospective study, whether inflammation status and cytokine profile could serve as additional biomarkers guiding treatment decision for single agent ICIs in NSCLC. 29 stage IV NSCLC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 28 publications
0
39
0
1
Order By: Relevance
“…Given that T-cell exhaustion is the self-protective mechanism for dysregulation of immune reaction, patients with impaired lung function might be vulnerable to ICI therapy as blockade of PD-1/PD-L1 pathway, causing airway injury, lung function decline, or pneumonitis. Additionally, analysis of circulating inflammatory markers related to ICI treatment such as neutrophil to lymphocyte ratio, LDH or CRP, which are widely used in previous studies, could provide more detailed inflammatory profiles for evaluation in the future investigation ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that T-cell exhaustion is the self-protective mechanism for dysregulation of immune reaction, patients with impaired lung function might be vulnerable to ICI therapy as blockade of PD-1/PD-L1 pathway, causing airway injury, lung function decline, or pneumonitis. Additionally, analysis of circulating inflammatory markers related to ICI treatment such as neutrophil to lymphocyte ratio, LDH or CRP, which are widely used in previous studies, could provide more detailed inflammatory profiles for evaluation in the future investigation ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, systemic inflammation can limit tumor-specific immunity and responses to the immune-checkpoint inhibitors (ICIs). In a recent study, systemic inflammation demonstrated by increased cytokine profiles was associated with poor survival and response to the ICIs in patients with lung cancer [ 56 ]. Therefore, blood viscosity can also be a biomarker for HCC patients treated with ICIs, and future large and prospective study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…proposed [64][65][66] . Moreover, IL-1α blocking agents have already been tested in clinical trials on patients with various tumors and with different grading, showing variable efficiency 41,42,44,64 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, considering the variability of cytokines levels and responses to cytokines-based therapies in patients 61 , IL-1α blockade could be envisaged as an alternative to IL-6 inhibition for boosting STAT3i 62 in those patients with low levels of IL-6 and low sensitivity to IL-6 depletion 63 . The specific cytokines expression profiling in patients, in fact, might be a useful tool to predict the patient response to the treatment and to design the best therapeutic strategy, according to the concept of personalized medicine, as previously proposed [64][65][66] . Moreover, IL-1α blocking agents have already been tested in clinical trials on patients with various tumors and with different grading, showing variable efficiency 41,42,44,64 .…”
Section: Discussionmentioning
confidence: 99%